ACCEPTANCE OF ISLAMIC MOBILE BANKING IN GIVING DONATION: DO TRUST AS A MEDIATION? - Roni Mohamad; Chitra Yuliashri Katili; Rifadli D Kadir (NISBAH: Jurnal Perbankan Syariah, 2023)
This study analyzes the interest in using donation payment services in Islamic bank mobile banking. Using the Technology Acceptance Model (TAM), variables that can affect interest are analyzed. Some of the variables used are Perceived Ease of Use (PEU), Availability of Islamic Features (AIF), Perceived Risk (PR), and Trust. This study specifically used trust variables as mediation. Data obtained using questionnaires to 118 respondents were then analyzed using SEM-PLS with Smart-PLS 3 software. The results of this study show that the Variable Availability of Islamic Features (AIF) is the primary variable in increasing trust, while Perceived Ease of Use and Perceived Risk are not following the hypothesis proposed. This research has implications for the development of Islamic banks, especially related to the use of donation payment service features using mobile banking. If it wants to increase interest in customers using mobile banking, especially in donation payments, Sharia banking must increase trust in Islamic banks.